Dependence of wear behavior on sintering mechanism for Iron-Alumina Metal Matrix Nanocomposites - Gupta P.; Kumar D.; Parkash O.; Jha A.K.; Sadasivuni K.K. (My University, 2025)
The present paper reports the dependence of wear behavior on sintering mechanism for iron (Fe) – alumina (Al2O3) metal matrix nanocomposites fabricated via Powder Metallurgy (P/M) technique. Nanocomposite composition was taken as 10 wt % Al2O3 and 90 wt % Fe. Synthesized green specimens were sintered in an argon atmosphere in the temperature range of 900–1100 °C for 1–3 h. XRD pattern of sintered nanocomposite reveals the formation of iron aluminate (FeAl2O4) phase beside presence of iron (Fe) and trace amount of aluminium oxide (Al2O3). Iron aluminate phase is formed as a result of reactive sintering between iron and alumina particles. Wear and coefficient of friction behavior of nanocomposite specimens were investigated under a load of 0.5, 1.0 and 2.0 kg with a constant sliding velocity of 4 m/s and sliding time of 1 h. It is found from these studies that the wear properties in nanocomposite specimen depends on the sintering temperature and sintering time respectively. © 2018 Elsevier B.V.